Modified lumped series resistance model of solar cells under shadow conditions - Sharma A.K.; Gopal R.; Dwivedi R.; Srivastava S.K. (My University, 2025)
The conventional lumped series resistance model of solar cells is inadequate to match experimental results quantitatively under shadow conditions. This is because of the inherent assumption in this model, that the geometrical series resistances are identical for both illuminated and dark portions of the cell. In fact, the series resistance in the dark case is always greater than that for the illuminated case. In order to take this problem into account, the conventional lumped series resistance model for the dark case has here been modified by adding an additional series resistance to that for the illuminated case. The enhanced series resistance has been simulated with the effective surface resistance of the emitter layer caused by current crowding phenomenon in the vicinity of the metallic grid. The calculated results are in excellent agreement with the observed data. © 1990.